(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: Optic disc pits (ODP) usually present with the serous maculopathy found in 30% to 75% of these patients. Purpose: To demonstrate the potential of optical coherence tomography angiography (OCTA) for monitoring the natural and postoperative course of ODP maculopathy. Materials and Methods: We present a case of a 27-year-old female patient with serous maculopathy associated with optic disc pit. OCTA scans were obtained using RTVue XR Avanti (Optovue, Fremont, CA). The OCTA-based vessel density was assessed. The follow-up after presentation was 10 months. Results: The development of maculopathy in this case was found to be associated with penetration of liquor from the subarachnoidal space through the intermembranous spaces of the optic nerve. It is important to monitor the pathological areas found with the use of OCT and OCTA not only intraoperatively, but also postoperatively. Complete blockage of fluid tracts was achieved, evidencing the efficacy of treatment measures. A decrease in vessel densities of the superficial retinal plexus in the foveal and parafoveal regions of the affected eye was accompanied by deterioration of visual functions, and guided the choice of treatment strategy. OCTA enables monitoring of morphological changes before and after surgical treatment and assist in making a prognosis for visual function.